Selection on MHC in a context of historical demographic change in 2 closely distributed species of tuco-Tucos (ctenomys australis and C. Talarum) - Cutrera, Ana Paula (2017)
Selection necessarily acts within the same current and historical demographic framework as neutral evolutionary processes, and the outcome of the interplay between these forces may vary according to their relative strength. In this study, we compare the variation at a major histocompatibility complex (MHC) locus (DRB exon 2), typically subject to strong diversifying selection, and mitochondrial diversity (D-loop) across populations encompassing the entire distribution of 2 species of South American subterranean rodents: Ctenomys australis and C.Talarum (tuco-Tucos). Although these species are parapatric along most of their distribution, historically they have followed distinct demographic trajectories associated with sea level changes during the Quaternary. We surveyed 8 populations of C. australis and 15 of C.Talarum, from which we analyzed 70 and 212 D-loop haplotypes and 91 and 346 DRB genotypes, respectively. Both species have gone through a recent demographic expansion; however, the signal of this process only encompasses the entire distribution of one of the species: C. australis. While balancing selection on MHC in C.Talarumenhanced DRB diversity at the local level compared to D-loop, although not promoting divergence among populations, in C. australis local diversifying selection may have driven higher population differentiation at DRB than at D-loop. Our findings reinforce the idea that the relative strength of selection acting on MHC genes varies spatially and temporally within and among species, even between species using the same macrohabitat and exposed to similar immune challenges.